2014
DOI: 10.7314/apjcp.2014.15.19.8057
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Utility for Predicting Biological Behavior of Invasive Ductal Breast Cancers

Abstract: Asian Pac J Cancer Prev, 15 (19), 8057-8062 IntroductionDetermination of the molecular status of invasive breast cancer is useful as a prognostic and predictive factor, and it has become standard practice in the management of breast cancer because estrogen receptor (ER) and human epidermal growth factor receptor2 (HER2) positivity predict response to endocrine therapy or targeted therapy with monoclonal antibodies directed against HER2 (Bauer et al., 2007;Doreen et al., 2011). If it is possible to predict mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Most malignant breast lesions are characterized by dense interstitial fibrosis; the cancer cells in the fibrous stroma infiltrate the lesion caused by nearby construction activity, thus reducing adhesion and decreasing elasticity. Benign lesions, such as fibroadenomas show hyperplasia of the glandular epithelial cells and the stromal cells, which are rich in mucopolysaccharides, therefore imparting a relatively loose texture (Zhang et al, 2014). Our results are in agreement with the observations made by Krouskop et al (1998), which showed that the levels of elastic stiffness varied with different breast tissues; the invasive carcinoma showed the lowest elasticity, followed by noninvasive carcinoma, fibrous tissue in the breast, normal glandular breast tissue, and breast fat tissue.…”
Section: Discussionsupporting
confidence: 83%
“…Most malignant breast lesions are characterized by dense interstitial fibrosis; the cancer cells in the fibrous stroma infiltrate the lesion caused by nearby construction activity, thus reducing adhesion and decreasing elasticity. Benign lesions, such as fibroadenomas show hyperplasia of the glandular epithelial cells and the stromal cells, which are rich in mucopolysaccharides, therefore imparting a relatively loose texture (Zhang et al, 2014). Our results are in agreement with the observations made by Krouskop et al (1998), which showed that the levels of elastic stiffness varied with different breast tissues; the invasive carcinoma showed the lowest elasticity, followed by noninvasive carcinoma, fibrous tissue in the breast, normal glandular breast tissue, and breast fat tissue.…”
Section: Discussionsupporting
confidence: 83%
“…Low grade HR+, HER- tumors were found to be more irregular in shape, with ill-defined margins, posterior shadowing and hyper- or complex echo. Conversely, high grade TN showed regular shape, a hypo- or complex posterior shadowing and posterior enhancement, similarly to other studies [ 45 , 46 ]. The echo pattern features were the most effective in the prediction of molecular subtypes.…”
Section: Radiomics and Molecular Subtypessupporting
confidence: 89%
“…Basal-like cancers, however, are not synonymous with TNBC, but often there is an overlap; also, both basal-like and TNBC show a strong association with the BRCA gene mutation. 12,15,16 The TNBC subtype of breast cancer remains an extraordinary challenge for the oncologists/surgeons who treat these patients. Triple-negative breast cancer often occurs in younger women, who present with a larger tumor and are more likely to have distant visceral metastasis and an early relapse, making the overall outcome poor.…”
Section: Discussionmentioning
confidence: 99%